Development of Unsupported Composite Alumina Sol/Poly(vinyl alcohol) Membranes For Glucose Oxidase Immobilization - Wong, Fui Ling; Abdul Aziz, Azila (2005)
An important aspect of biosensor developments is the immobilization method of the sensing agent within the solid matrix. In the continuous search for a suitable support material for glucose oxidase, a composite membrane of alumina sol(AlOOH)/poly(vinyl alcohol)(PVA) was investigated. The alumina sol was prepared using aluminium iso-propoxide via the sol-gel process. PVA was employed as the organic binder to enhance the mechanical strength of the porous sol-gel membranes. The ability of the composite membrane in retaining glucose oxidase and the apparent enzyme activities of the composite membranes were studied. The resulting composite membranes were found to be crack-free, stable and still very active after 60 days. However, the enzyme leakage period was observed to be quite long. The enzyme was still leaking from the membrane after more than 400 hours albeit at a very low level.